J/ψ, Y and B meson production in proton–proton collisions at the LHC - Kotlyar, V.V.; Krupina, N.V. (Вопросы атомной науки и техники, 2012)
Mechanisms of J/ψ, Υ and B meson production in proton-proton scattering at total energy 7 TeV are studied with the help of event generator Pythia 8. Uncertainties in the total and differential cross sections due to choice of the renormalization and factorization scales are analyzed for prompt J/ψ and Υ production. Sensitivity of the inclusive cross sections on contributions of J/ψ from decay of b–hadrons is also discussed. Results of the calculations are compared with the ALICE, ATLAS, CMS, and LHCb data in order to assess potentialities and validity of the approaches, in particular color singlet and octet models, used in the simulations.